Abuse of immediate-release opioids and current approaches to reduce misuse, abuse and diversion. Issue 4 (19th May 2022) - Nalamachu, Srinivas R.; Shah, Binit
ABSTRACT: Deaths from opioid overdoses have increased dramatically over the past few years. Given that immediate-release (IR) opioids account for most of the U.S. market share, and that abusers generally prefer IR opioids over extended-release (ER) opioids, it is not surprising that rates of abuse are higher for IR than ER opioids. IR opioids are widely prescribed, often without consideration for risks of abuse, misuse, and diversion. Prescription opioid abuse and misuse often begins through oral administration and progresses into non-oral routes (e.g. snorting, injecting) as abusers gain more experience; non-oral routes carry heightened safety concerns. Current approaches used for reducing opioid abuse include U.S. Food and Drug Administration regulations, state legislation, insurance company policies, the use of multimodal analgesic therapy, patient risk assessment and monitoring, limiting access to opioids by reducing IR opioid prescription quantity and length, prescription drug monitoring programs, patient education on proper disposal of unused medication and risks of diversion, as well as abuse-deterrent formulations. Albeit, most abuse-deterrent formulations have focused on ways to prevent the circumvention of ER characteristics rather than placing obstacles to abuse of IR opioid formulations. Reducing opioid abuse requires the combined efforts of multiple stakeholders, including prescribing clinicians, patients, pharmacists, nurses, insurance companies, government agencies, and pharmaceutical companies.